A Case of Secondary Hemophagocytic Lymphohistiocytosis in a Patient With Acute HIV Infection - Yiliam Castillo; Liorge Dominguez; Antonio Crespo; Julio J. Alvarez Cardona (Annals of Internal Medicine: Clinical Cases)
A 22-year-old man who has sex with men with no significant medical history presented with a 2-week history of fever and right upper abdominal pain. Initial blood tests revealed leukopenia, thrombocytopenia, and elevated liver enzymes. The diagnosis of secondary hemophagocytic lymphohistiocytosis (HLH) was supported by fever, splenomegaly, hypertriglyceridemia, hyperferritinemia, and high soluble interleukin-2 receptors, meeting the 5/8 criteria of the Histiocyte Society-2004. Further laboratory tests indicated an elevated HIV RNA viral load, supporting a diagnosis of acute HIV infection. Our case suggests that identifying acute HIV infection as a trigger for secondary HLH is crucial for enabling prompt initiation of therapy, potentially preventing fatal outcomes.